A Review of Microfluidic Chips Applications in Biological Diagnosis - Saeed Parhoodeh; Ghader Allahverdi (Fasa University of Medical Sciences, 2019)
Recent advances in science and technology caused the Revolution in many different fields of science and Industry. The term lab on a chip or performing difficult analyses only in a short time and in a small space is an expression which becomes very common in recent years. Today, the things which were wishes in the past, are becoming real and inserted in the real life of humankind. In this article, it is tried to study and discuss a special kind of lab on a chip technology, which is called microfluidic (or microchannel). Although this is a vast technology, and it was inserted in many branches of Science and Industry, but here, we have discussed only the applications of this technology in medical and biological diagnostic fields. In this article, we have especially surveyed the devices which were made based on this technology for DNA analysis, devices for detection based on separation, devices for cell sorting and handling and devices for protein-based applications.